Obesity prevalence in relation to gut microbial environments capable of producing equol or O-desmethylangolensin from the isoflavone daidzein - Frankenfeld, Cara L. (2014)
BACKGROUND: Studies have observed associations between the gut microbiome and obesity. O-desmethylangolensin (ODMA) and equol are gut bacterial metabolites of daidzein, a compound found in high amounts in soy foods. Approximately 80–95% and 25–60% of individuals harbor gut microbial communities capable of producing ODMA or equol, respectively. Given that other phenotypes of gut bacterial metabolism of dietary compounds have been associated with obesity, we hypothesized that daidzein-metabolizing phenotypes would be associated with obesity. OBJECTIVE: To compare the prevalence of ODMA-producer and equol-producer phenotypes in obese, overweight, and normal weight individuals. METHODS: Adults aged 18 to 95 years (n=297) provided a first-void urine sample after a three-day soy challenge, and urinary ODMA and equol concentrations were used to classify individuals as producers or non-producers. Body mass index was calculated from self-reported weight and height. RESULTS: There were 60 ODMA non-producers and 173 equol non-producers. Obese individuals were 2.8-times more likely to be ODMA non-producers (OR=2.8, 95% CI: 1.2, 6.2) compared to normal weight individuals, when adjusted for age, race (white vs. non-white), and gender and menopausal status (male, premenopausal female, and postmenopausal female). Obesity was not associated with equol-producer phenotype (OR=1.1, 95% CI: 0.5, 2.2). Stronger associations with obesity were observed in the ODMA non-producers who were also equol producers than equol non-producers. CONCLUSIONS: Results from this analysis suggest that the ODMA-producer phenotype, but not equol-producer phenotype, is associated with obesity in adults. These results support further work to replicate these findings and evaluate mechanisms of the observed associations.